Characterization of Chemical Properties of Inulin Isolated from Yacón Tuber - Dimas Andrianto; Maria Bintang; Irfan Abdul Aziz; Suci Hermita (Jurnal Teknologi dan Industri Pangan, 2022)
Inulin is a polysaccharide with linear fructan chain structure. Food industries widely use inulin as a low calorie sugar substitutions. Yacón (Smallanthus sonchifolius) tuber that are easily grown and contain higher inulin can be explored as local inulin sources. This research aimed to characterize the chemical properties of inulin isolated from yacón tuber. The methods of this study include proximate analysis of yacón tuber, inulin isolation, and characterization of purified inulin using FTIR. The results showed that yacón consisted of 91.23 water (analyzed as moisture), 0.12 proteins, 0.58 fats, 0.52 crude fibers, and 7.34% carbohydrates. The yield of inulin extracted from yacón tuber was 4.86% whereas its purity and actual content of inulin were 44.23 and 2.15%, respectively. The Osazon test revealed that the isolated inulin has similar crystalline with that from chicory. Based on characterization using the FTIR spectrophotometer, the isolated inulin had functional groups of C-O, C-H, CH2, O-H, and C=O. The spectrum of the isolated inulin has similarities with chicory inulin. Therefore, yacón tuber could be considered as a potential local inulin source in Indonesia.